ANALISIS BISNIS PENGEMBANGAN AGROINDUSTRI GULA MERAH KELAPA SAWIT DI DESA PEGAJAHAN KABUPATEN SERDANG BERDAGAI - Nasution, Khairunnisyah; Rafinda, M. Syarif; Adelia, Fanny (Agriprimatech, 2024)
This study aims to analyze the development strategy of brown sugar agroindustry to eight palm oil and to identify the factors of development of brown sugar agroindustry to eight palm oil in Pegajahan Village, Serdang Bedagai Regency. This research uses SWOT Analysis methods, namely Strenght (Strength), Weakness (Weakness), Threats (Threat), and Op-portunity (Opportunity). Internal factors in a business include strengths and weaknesses, while external factors include opportunities and threats. The results of the study were used, there are internal factors that include (strengths and weaknesses), it can be seen that the strength factor in the palm oil brown sugar business has the highest rating is in products recognized by the public / marketing is quite broad and internal factors that are indicators of weakness of the highest rating are not yet having a brand. While external factors (opportunities and threats) can be seen from the opportunity to have the highest rat-ing, namely high market demand, and the factor that is the highest rating threat indicator is No government assistance.